Two-photon polymerization based large scaffolds for adhesion and proliferation studies of human primary fibroblasts. (October 2018) - Trautmann, Anika; Rüth, Marieke; Lemke, Horst-Dieter; Walther, Thomas; Hellmann, Ralf
Highlights: Scaffolds in the range of several millimeters fabricated in 6.3 min. Implementation of a highly efficient single-line single-pass fabrication process. Study of post-processing steps to avoid toxicity. Cell adhesion, proliferation, and survival on the scaffolds. Three-dimensional cell growth without the support of previous protein coating. Abstract: We report on cellular adhesion of human primary fibroblasts on scaffolds fabricated by laser-induced two-photon polymerization using 515 nm femtosecond pulses. The scaffolds are large scaled with a dimension in the range of several millimeters and consist of a periodic reproducible structure. A minimum process duration of 6.3 min is achieved by an implemented nonstop single-line single-pass fabrication process and allows to write several identical specimens with different pore sizes from 10 µm up to 90 µm suitable for cell adhesion studies in a reasonable amount of time. OrmoComp®, an organic-inorganic hybrid polymer, is chosen as base material for the structures. Human dermal fibroblasts are directly seeded on scaffolds after several post-processing steps to ensure the extraction of toxic residues. Cell adhesion, proliferation, and survival are examined after three, six, and nine days of culture, respectively. Cell growth is compared depending on the different pore sizes of the scaffolds. Due to the horizontal and vertical cell growth observed on and inside the structures, we demonstrate that large scaffolds prepared from OrmoComp® qualify for three-dimensional cell adhesion and growth without support of an additional protein coating.